Pemanfaatan Sistem Informasi Geografis (Gis) Untuk Mengetahui Lokasi Penjual Tiket Bus Di Kota Solo Berbasis Android - Setiadi, Rafli, Dr. Bana Handaga, M.T (2016)
The bus is one of the type of transportation used by people of Solo, with many enthusiasts in this mode of transportation is needed resources that can help prospective passengers to know the name of the bus and a bus ticket seller accurate and practical. The information system was created for android smartphone with android studio use and application of information systems is a technology-based Location Based Service (LBS) and SQLite database management. For facilities in the information system is equipped with a display map and route guidance path to realtors bus tickets in the city of Solo by utilizing the Google Maps API that can be accessed with the condition online, to determine the user's position using the Global Positioning System ( GPS ) contained in android device. This information system is expected to help people to more easily access or seek realtors bus tickets in the city of Solo in accordance with the closest distance to the bus at the user or users enjoy . The results of this research is to create an android GIS -based information system to help the public to the ocation of the pool and bus ticket agent in Solo city and several surrounding . This application has been through the testing phase values obtained 4,155 of scale 1-5.